Abraham Epstein the forgotten father of social security - Epstein, Pierre (University of Missouri Press, 2006)
"Pierre Epstein takes readers behind the scenes of Roosevelt's New Deal legislation to tell how his father, Abe Epstein, an immigrant Russian Jew and author of "Insecurity: A Challenge to America," followed his vision of reform and made significant contributions to the legislation that established social security in America"--Provided by publisher.